Immaterial Error Corrections and Financial Reporting Reliability* - Choudhary, Preeti; Merkley, Kenneth; Schipper, Katherine (Contemporary Accounting Research, 2021)
ABSTRACT We provide large‐sample archival evidence on the nature and consequences of errors deemed immaterial to the previously issued financial statements containing the errors (immaterial errors). The incidence of immaterial error corrections has been increasing since about 2004, and these corrections are associated with modestly and discernibly negative share returns that are more negative for income‐decreasing corrections and corrections that involve multiple issues. We find that immaterial errors are a leading indicator of poor reporting reliability as measured by future material and immaterial reporting errors, material weaknesses in internal controls, and SEC comment letters. Our findings suggest that immaterial errors provide researchers and investors with a more frequent and less severe indicator of potential audit or financial reporting issues as compared to more extreme reporting problems such as material errors corrected by restatements.